2011
DOI: 10.1007/s11250-011-9957-3
|View full text |Cite
|
Sign up to set email alerts
|

Domestic livestock resources of Turkey

Abstract: Water buffalo are an ancient component of Turkey's domestic livestock resources. Commonly referred to as the Anatolian buffalo the animal is part of the Mediterranean group which includes Syrian, Egyptian and Southeast European animals. Once quite numerous, there have been drastic reductions in their numbers since the 1970s due to intensification of dairy activities, agricultural mechanization and changing consumer preferences. The main areas of distribution are in northwest Turkey in the Marmara and Black Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 6 publications
(5 reference statements)
0
33
1
3
Order By: Relevance
“…Coat colour varies from dark black to light black or brown. Body coat is covered with long hairs (Akdağ and Çelik, 2006;Atasever and Erdem, 2008;Soysal, 2009;Yilmaz et al, 2012). Water buffalos had been used as draught animals in Balkan, Mediterranean and Middle-East countries for centuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coat colour varies from dark black to light black or brown. Body coat is covered with long hairs (Akdağ and Çelik, 2006;Atasever and Erdem, 2008;Soysal, 2009;Yilmaz et al, 2012). Water buffalos had been used as draught animals in Balkan, Mediterranean and Middle-East countries for centuries.…”
Section: Introductionmentioning
confidence: 99%
“…Water buffalos had been used as draught animals in Balkan, Mediterranean and Middle-East countries for centuries. Water buffalos are well adapted to extensive production system with poor feeding and management conditions, and have relatively better disease resistance than cattle (Soysal, 2014;Yilmaz et al, 2012). Although the number of water buffalos in the world slightly increased during past three decades, water buffalo population in the certain Balkan countries (Turkey, Romania, Bulgaria) has decreased drastically (Borghese and Mazzi, 2005;FAO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that milk production increased between days 16 and 60 (11.35 kg/per head), that fatty content was higher (P ≤ 0.01) at the end of the peak production period (8.64%), and that protein levels increased at the onset and end of lactation (4.84 vs. 4.93). Finally, Yilmaz et al (2012) reported milk yields of 24-26 l/day during a lactation period of 225 ± 6 days. Total milk solids were 17.7 ± 0.3%, protein was 4.2 ± 0.1%, and fat was 8.1 ± 0.2%.…”
Section: Milk Productivitymentioning
confidence: 99%
“…In Asia, the domestic water buffalo is generally classified into two principal sub-species (Yue et al 2013); the river type and the swamp type (Perera 2008). These sub-species have distinct chromosome karyotypes (50 and 48 chromosomes, respectively) (Yilmaz et al 2012), and some differences in morphology (body frame, body weight, horn shape, skin colour) and behaviour (i.e., wallowing in water vs. mud). The best-known breeds are Murrah, Mediterranea, Jaffarabadi, Nili-Ravi, Surti, Mehsana, Kundi, Nagpuri and Bhadawari (Bartocci et al 2002;Cruz 2007;Das et al 2008;Thiruvenkadan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The individual properties of the related loci of the cattle races can affect the DGAT1 K232A polymorphism and this may produce different effects on milk fat [4,5] . The utility of the cattles for milk and meat production, their adaptation to natural conditions and tolerance to diseases makes them economically advantageous [6,7] . Due to the mentioned reasons, the investigations of K232A polymorphism in cattle plays an important role in in milk industry and procurement of higher quality milk, thus consumer health.…”
Section: Comparision Of Dgat1 K232a Polymorphism and Its Effects On Smentioning
confidence: 99%